Reverse Logistics for Solid Waste from the Construction Industry - Manuel Vargas; Miguel Alfaro; Natalia Karstegl; Guillermo Fuertes; María D. Gracia; Julio Mar-Ortiz; Jorge Sabattin; Claudia Duran; Naudy Leal (Advances in Civil Engineering)
This article reviews studies on the application of reverse logistics in solid waste from the construction industry. The main objective is to provide a summary of current knowledge and specific areas for future research. In addition, construction, as an economic sector, is in a continuous search for new tools to improve its processes, so this research provides the current situation of the relationship between reverse logistics and solid waste in the industry. The review methodology was content analysis of scientific literature published between 1997 and 2020, and total of 66 articles were used. 73% correspond to research articles, around 13% are case studies, and 12% are literature reviews. Only one of the articles is a survey. In addition, 52% of the works reviewed correspond to solid waste studies and 49% are related to the construction industry; only one publication does not classify in any. The most used keywords for the identification of published works were reverse logistics and supply chain; both terms are frequently related to the process and general management of solid waste and construction. The least used term was the literature review that shows the low number of articles that provide a summary of the proposed topic. Finally, three materials were chosen for the study because they are the most used in construction: metals, bricks, and concrete. 15% of the articles study all three, 18% study only metals, and 63% study other materials or are related to construction and solid waste in general.